(3TbGFb GdCJQL aj QbGFb GdZfLs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg hcai , hSdGe Ydi YHGOg GdPjf GUWai gPG LRA jSei HTbGFb GdCJQL ai QbGFb GdZfL , CdaJg LhGHkG dSGFd Yf Mceg TQYkG hChQOJ ajg ef GdahGFO eGdGjRjO Ydjg LeYkG s
(3BNQgG (B:s
(3hCfTO ai GdMeGSI dQLd jgLh CeQCJg (B: (3hJaJQ Yf adL YOeJ MOjKgG hYf LHdi WF hYf gQei eUQ s
(3Ydi MhGTjgG JUMjMGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B128 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B534s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GcJGH GdKGfi (B- (3U (B141 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(1072 (3c(B) s
Keywords: (3GdWHs